Pesticides With Potential Thyroid Hormone-Disrupting Effects: A Review of Recent Data - Leemans, Michelle; Couderq, Stephan; Demeneix, Barbara; Fini, Jean-Baptiste (Frontiers in Endocrinology, 2019)
Plant Protection Products, more commonly referred to as pesticides and biocides, are used to control a wide range of yield-reducing pests including insects, fungi, nematodes and weeds. Concern has been raised that some pesticides may act as endocrine disrupting chemicals (EDCs) with the potential to interfere with the hormone systems of non- target invertebrates and vertebrates, including humans. EDCs act at low doses and particularly vulnerable periods of exposure include pre- and perinatal development. Of particular concern is the number of pesticides with the potential to interfere with the developing nervous system and brain, notably with thyroid hormone signalling. Across vertebrates, thyroid hormone orchestrates metamorphosis, brain development and metabolism. Pesticide action on thyroid homeostasis can involve interference with TH production and its control, displacement from distributor proteins and liver metabolism. Here we focused on thyroid endpoints for each of the different classes of pesticides reviewing epidemiological and experimental studies carried out both in in vivo and in vitro. We conclude first, that many pesticides were placed on the market with insufficient testing, other than acute or chronic toxicity, and second, that thyroid-specific endpoints for neurodevelopmental effects and mixture assessment are largely absent from regulatory directives.